From Tai-isation to Lao-isation: Ethnic changes in the longue durée in Northern Laos - Évrard, Olivier (The Australian journal of anthropology, 2019)
This article uses ethnographic data collected since 1994 in Northern Laos to reassess the modalities of Tai cultural and political influence on the Khmu, a Mon-Khmer-speaking highland population, and to understand why, after so many years of ‘Tai-isation’, distinct identities still exist. For Grant Evans, who conducted fieldwork in Tai-Dam and Sing Moon (Ksing Mul) villages at the end of the 1980s, the answer lay in the fundamentally dualistic character of Tai-isation, which both favours assimilation and also tends to perpetuate interethnic boundaries. I will here insist on the fact that Tai-isation does not imply only the influence of the Tai on the highland peoples’ way of life but also how the latter adapt themselves to this influence with their own cultural resources. Tai-isation is traditionally an inclusive and therefore ambivalent process which can lead both to the assimilation of some highlanders and simultaneously to the emergence of new identity markers, myths or categories, which transform and structure interethnic relationships. State-building and Lao nationalism have nonetheless profoundly reshaped these dynamics and Lao-isation now operates in a radically different conceptual framework.